Three essays on corporate finance - Sun, Rui (2017)
This dissertation comprises three essays on corporate finance. Essay one documents that the generalized public trust in companies held by residents of a state reduces the likelihood of financial misstatements made by public firms headquartered in the same state. A closer examination reveals that public trust can only significantly reduce the likelihood of misstatements due to reporting errors, but it is ineffective in reducing misstatements due to irregularities. This implies that honest managers prefer to maintain the trust placed in them and take more care not to accidentally misstate, while dishonest managers dismiss or exploit public trust. The above findings are consistent with the idea that corporate culture is aligned with local culture, and can also be partly explained by managers’ concern about investors’ opinions, since my results show that stock market reactions to restatements are more negative for firms located in more trusting states. Additional evidence also supports that public trust has limited impacts when earnings are manipulated in an obscure way, or when corporate governance is poor. Essay two investigates how private firms allocate internally generated cash flow by estimating the cash flow sensitivities of various uses of cash flow. Our results reveal that, compared with public firms, private firms allocate less cash flow to investments and cash saving, and direct more to dividends and reduction of external finance, especially debt. The above pattern remains robust if we apply various matching schemes or if we only look at the transitory cash flow shock. To find out what is the driving force of private firms’ cash flow allocation, we attempt to draw parallel evidence from public firms, but find that the analysis within public firms cannot be applied mechanically to private firms. Special features of private firms – more concentrated equity ownership, more powerful shareholders with a strong desire for liquidity and diversification, and higher agency costs associated with debt finance are very likely to play a vital role in shaping their cash flow allocation. Essay three studies the impact of Stop Trading on Congressional Knowledge (STOCK) Act on congressional stock trading. Using hand-collected congressional financial disclosure data, we find that the frequency, dollar volume, timing ability, and profitability of congress trading have been reduced much after the STOCK Act, and especially so in purchase transactions which better reflect the activeness of potentially informed trading. A parallel study using CEO insider trading data does not exhibit such changes around the passage of this law, which points to the causality relationship flowing from the STOCK Act to changing congressional trading patterns.